2011
DOI: 10.1186/1472-6882-11-58
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Agaricus bisporus and Agaricus brasiliensis show similarities in their structures and their immunomodulatory effects on human monocytic THP-1 cells

Abstract: BackgroundMushroom polysaccharides have traditionally been used for the prevention and treatment of a multitude of disorders like infectious illnesses, cancers and various autoimmune diseases. Crude mushroom extracts have been tested without detailed chemical analyses of its polysaccharide content. For the present study we decided to chemically determine the carbohydrate composition of semi-purified extracts from 2 closely related and well known basidiomycete species, i.e. Agaricus bisporus and A. brasiliensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 39 publications
(63 reference statements)
3
58
1
1
Order By: Relevance
“…Numerous healthpromoting effects of A. brasiliensis have been scientifically proved (Wei and Van Griensven 2008, Hetland et al 2008, Kozarski et al 2011, Roupas et al 2012. Antigenotoxic, anticarcinogenic, antimutagenic and antitumor activities have been described (Guterres et al 2005, Mantovani et al 2008, Kim et al 2009, Ishii et al 2011) and a wide range of immunomodulatory properties (Johnson et al 2009, Ishii et al 2011, Kozarski et al 2011, Smiderle et al 2011, 2013. All these beneficial effects of A. brasiliensis were demonstrated on mammals or mammalian cells in vitro and with the aim of promoting human health.…”
Section: Honey Bees Apis Mellifera L (Hymenopteramentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous healthpromoting effects of A. brasiliensis have been scientifically proved (Wei and Van Griensven 2008, Hetland et al 2008, Kozarski et al 2011, Roupas et al 2012. Antigenotoxic, anticarcinogenic, antimutagenic and antitumor activities have been described (Guterres et al 2005, Mantovani et al 2008, Kim et al 2009, Ishii et al 2011) and a wide range of immunomodulatory properties (Johnson et al 2009, Ishii et al 2011, Kozarski et al 2011, Smiderle et al 2011, 2013. All these beneficial effects of A. brasiliensis were demonstrated on mammals or mammalian cells in vitro and with the aim of promoting human health.…”
Section: Honey Bees Apis Mellifera L (Hymenopteramentioning
confidence: 99%
“…Mushroom cultivation and extract preparation were described previously (Wei andVan Griensven 2008, Savić et al 2011). GC-MS and NMR spectroscopy (Smiderle et al 2011(Smiderle et al , 2013 showed that the extract was rich in polysaccharides (45.9 g/100 g), mostly glucans (40.1 g/100 g): α-glucans 17.3 g/100 g and β-glucans 22.8 g/100 g During the experimental period, colonies were regularly checked for both bee and brood pathology by a veterinary specialist, following the instructions of the "Office International des Epizooties" (OIE 2013). Varroa destructor infestation was controlled twice a year with taufluvalinat (Varotom®, Evrotom, Ruma, Serbia).…”
Section: Mushroom Extractmentioning
confidence: 99%
“…Immunomodulation by food has the advantages of simplicity, low side effects and greater accessibility for low-income population groups. Results of in vitro experiments have demonstrated immunomodulatory effects of fungal β-glucans [2,3] and are described in details below. Moreover, positive effects of immunomodulation by food have already been described in humans [4].…”
Section: Immunomodulation In Atopic Diseasementioning
confidence: 99%
“…A. subrufescens Peck) is a Brazilian mushroom closely related to A. blazei Murrill (sensu Heinemann). In vitro and in vivo studies have shown mainly immunomodulatory [3,4,5], antitumoral [6], antigenotoxic [7], and antioxidant [3] activities for polysaccharides isolated from A. brasiliensis fruiting bodies and mycelia.…”
Section: Introductionmentioning
confidence: 99%